Encapsulation of calcium carbonate with a ternary mixture of sodium caseinate/gelatin/xanthan gum to enhance the dispersion stability of solid/oil/water emulsions - Zhang, Jie; Cao, Yanping; Xu, Duoxia (Frontiers in Nutrition, 2022)
The solid/oil/water (S/O/W) emulsion stabilized by sodium caseinate (NaCas), gelatin (GEL), and xanthan gum (XG) ternary composite was to improve the dispersion stability of calcium carbonate (CaCO3) in emulsions. Particle size, Zeta potential, physical stability, and microstructure were determined to characteristic the stability of the S/O/W emulsions. Shear rheological and tribological analyses were used to characterize the rheological properties of S/O/W emulsions. X-ray diffraction (XRD), Infrared spectral analysis (FTIR), and molecular docking were used to characterize the molecular interactions, which was to explore the influence of the W phase on the system stability. It was found that when the NaCas concentration was 2 wt% and the S/O phase addition was 5%, the particle size distribution was uniform, and the physical stability was improved. CLSM and Cryo-SEM results showed that the S/O/W emulsions could embedded CaCO3 in the system, and formed a dense three-dimensional network space structure. The viscosity of the system increased and even agglomeration occurred with NaCas concentration increased, and the stability of the emulsion decreased. XRD results confirmed that the CaCO3 was partially covered due to physical embedding. Infrared spectral analysis and molecular docking results showed electrostatic, hydrophobic interaction, and hydrogen bond interaction between NaCas, GEL, and XG, which could improve the stability of S/O/W emulsions. The results showed that the S/O/W emulsions delivery system is an effective way to promote the application of CaCO3.